Epithelioid Malignant Peripheral Nerve Sheath Tumor in the Liver: Report of a Rare Unusual Case with Rhabdoid Morphology and Review of the Literature. (18th February 2022) - Van Treeck, Benjamin J.; Said, Samar; Yasir, Saba
Abstract : Malignant peripheral nerve sheath tumor (MPNST) is a rare aggressive type of sarcoma. The epithelioid variant of MPNST has a distinctive morphology and immunophenotype, which can be a diagnostic challenge when it arises in an unusual location. Awareness of these morphologic entities is essential to make an accurate diagnosis. Here, we report a case of epithelioid MPNST involving the liver. The tumor displayed rhabdoid morphology and an unusual immunophenotype. The report also discusses histopathologic features, molecular alterations, and the differential diagnoses of this rare entity.